Fuyuan Decoction Enhances SOX9 and COL2A1 Expression and Smad2/3 Phosphorylation in IL-1β-Activated Chondrocytes. (7th December 2015) - Zhang, Yudi; Li, Rongheng; Zhong, Yu; Zhang, Sihan; Zhou, Lingyun; Shang, Shike
Abstract : Fuyuan Decoction (FYD), a herbal formula in China, has been widely used for osteoarthritis (OA) treatment. Herein, we determined the effects of FYD on the expression of transcription factor SOX9 and its target gene collagen type II, alpha 1 (COL2A1) as well as the activation of Smad2/3 in interleukin- (IL-) 1 β -stimulated SW1353 chondrosarcoma cells. Serum-derived FYD (FYD-CS) was prepared to treat SW1353 cells with or without SB431542, a TGF- β 1 receptor inhibitor. Cell cycle progression was tested by flow cytometry. The expression of SOX9 and COL2A1 and the activation of Smad2/3 (p-Smad2/3) were analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and/or western blot. The results showed that, after treatment, FYD-CS, while inducing S-phase cell cycle arrest, enhanced cell proliferation and protected the cells against IL-1 β - and/or SB431542-induced cell growth inhibition. Furthermore, FYD-CS reversed the decreased expression of COL2A1 and SOX9 induced by IL-1 β and SB431542 and blocked the decreased phosphorylation of Smad2/3 induced by IL-1 β alone or in combination with SB431542. Our results suggest that FYD promotes COL2A1 and SOX9 expression as well as Smad2/3 activation in IL-1 β -induced chondrocytes, thus benefiting cell survival.